Innovations and emerging technologies in wound care - Gefen, Amit (Academic Press, an imprint of Elsevier, 2020)
"Innovations and Emerging Technologies in Wound Care is a pivotal book on the prevention and management of chronic and non-healing wounds. The book clearly presents the research and evidence that should be considered when planning care interventions to improve health related outcomes for patients. New and emerging technologies are discussed and identified, along with tactics on how they can be integrated into clinical practice. This book offers readers a bridge between biomedical engineering and medicine, with an emphasis on technological innovations. It includes contributions from engineers, scientists, clinicians and industry professionals. Users will find this resource to be a complete picture of the latest knowledge on the tolerance of human tissues to sustained mechanical and thermal loads that also provides a deeper understanding of the risk for onset and development of chronic wounds."--